Human identification using dental radiograph - Fahad, Salem Quddus; Hasan, Md. Nazmul; Sultana, Sharmin; Rabbani, Golam Shams (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.